THE ROLE OF A SCHOOL PSYCHOLOGIST IN WORKING WITH GIFTED STUDENTS: THEORETICAL FOUNDATIONS AND PRACTICAL MECHANISMS - Saitqulova , Iroda (INTERNATIONAL MULTIDISCIPLINARY SCIENCE CONFERENCE, 2026)
This scientific article is devoted to the theoretical and practical analysis of the significant role of a school psychologist in the educational system when working with gifted and talented students (adolescents). Identifying giftedness, understanding its psychological characteristics, and preventing social-emotional adjustment problems are considered among the primary responsibilities of a school psychologist. The article examines contemporary models of giftedness, methods of psychological diagnostics, and differential approaches to supporting gifted students.